THE IMPACT OF 2,4-DIAMINOBUTYRIC ACID ON PROTEINS INVOLVED IN THE DEVELOPMENT OF MORPHOMETRICALLY MEASURABLE EYE PARAMETERS IN ZEBRAFISH: AN IN SILICO ANALYSIS - Milošević, Milica; Mitović, Nikola; Ristić, Maša; Dimitrijević, Ljubica; Kovačević, Sanjin; Nešović-Ostojić, Jelena; Stanojević, Marija; Spasić, Svetolik (HEALTH CARE, 2024)
Introduction/ Aim: 2,4-Diaminobutyric acid (2,4-DABA) is an excitatory amino acid with neurotoxic, hepatotoxic, and potentially carcinogenic effects, found in aquatic ecosystems with a tendency to accumulate in plants and animals. Due to its potential impact on development, its embryotoxicity is being studied. Zebrafish (Danio rerio), with high homology to the human genome, serve as an excellent model for studying development and developmental abnormalities. Aim is to investigate the effect of 2,4-DABA on proteins crucial for zebrafish eye development using molecular docking.Methods: Proteome screening was conducted using the FINDSITEcomb software, selecting 1119 proteins based on homology, tissue specificity, and expression timing. Six proteins that met the criteria were analyzed using molecular docking in the AutoDock Vina program. Results: The interaction of the fzd8a protein with 2,4-DABA showed the lowest Gibbs free energy value of -4.6 kCal/mol, while the interaction with the pbx4 protein had the highest value of -3.4 kCal/mol. A similarity was observed in the amino acid sequence of proteins that bind to 2,4-DABA, particularly in those containing an –SH group.Conclusion: 2,4-DABA may affect eye structure development in zebrafish by interacting with proteins throughout the entire development period. The results of in silico analyses provide a basis for further in vivo research, which should be conducted on live embryos to confirm these findings.
Keywords: bioinformatics, eye development, 2,4-DABA, zebrafish